2011
DOI: 10.1590/s0102-05362011000200018
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de irrigação para cultivo de alface em ambiente protegido

Abstract: A alface (Lactuca sativa L.) é uma hortaliça cultivada em todo o Brasil. No Sub Médio São Francisco, as condições edafoclimáticas favoráveis à irrigação, possibilitam o seu cultivo durante todo o ano, principalmente em hortas comunitárias. O sistema produtivo usualmente adotado, em campo aberto, não contempla a quantificação da lâmina de irrigação necessária e nem a exploração de cultivares superiores, caracterizadas pela alta produtividade e tolerâncias às viroses.O cultivo de hortaliças em ambiente protegido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
2
12
0
6
Order By: Relevance
“…An evaporation mini-tank was used (minimized class A tank) for evaporation estimation. The mini-tank Kp adopted value was 1, which was also adopted by BANDEIRA et al (2011). The adopted Kc (0.60, 0.8, 1.05 and 1.0) was recommended by MAROUELLI, SILVA and SILVA (1996).…”
Section: Methodsmentioning
confidence: 99%
“…An evaporation mini-tank was used (minimized class A tank) for evaporation estimation. The mini-tank Kp adopted value was 1, which was also adopted by BANDEIRA et al (2011). The adopted Kc (0.60, 0.8, 1.05 and 1.0) was recommended by MAROUELLI, SILVA and SILVA (1996).…”
Section: Methodsmentioning
confidence: 99%
“…It was also observed that all of these evaluated variables were near field capacity (10 kPa) and safe from negative effects of water deficit. Thus, it is possible to assume that exposing plants to hydric stress induces water potential decline in leaves, stomatal conductance and CO 2 flow, resulting in an adverse impact on photo-assimilated compound accumulations and as consequence crop yield (BANDEIRA et al, 2011). Regarding hydric stress, each species has survival mechanisms that might include changes in stomatal responses, osmotic adjustment and major movement of photoassimilates to the roots, consuming metabolic energy and affecting plant production and commercial quality.…”
Section: Variationmentioning
confidence: 99%
“…Despite the relevance of protected environment cultivation in Brazil, there is a lack of research on subsidization and potential exploitation of this technology at different climatic regions, especially with regards to irrigation management (SANTOS & PEREIRA, 2004;BANDEIRA et al, 2011;VILAS BOAS et al, 2012). Such studies could optimize irrigation water use, enhancing crop yields and quality, especially for cultivars of high productive capacity.…”
Section: Introductionmentioning
confidence: 99%
“…A quantidade da água de irrigação aplicada nos tratamentos foi determinada de acordo com Bandeira et al (2011). Utilizaram-se os dados obtidos pelo tanque classe "A", instalado na área do experimento e a área dos vasos.…”
Section: Methodsunclassified